Profile of Creativity in Mathematical Problem Solving in terms of Self-Efficacy and Gender - Asmaul Husnah Amri; Suryanti Suryanti (Universitas Negeri Makassar, 2021)
This research is a qualitative research that aims to determine the profile of creativity in solving mathematical problems in terms of self-efficacy and gender in class X SMKN 4 Bone. The subjects in this study were X students of SMKN 4 Bone Pinrang which consisted of 4 subjects namely one male with high self-efficacy, one female with high self-efficacy, one male with low self-efficacy and one female with high self-efficacy. - low efficacy. The instrument used is the researcher himself as the main instrument assisted by self-efficacy tests, math problem solving tests and interviews designed to suit creativity. Data was collected by means of task analysis and interviews. The collected data were analyzed using qualitative content analysis techniques. The results of the study show that: 1) the profile of creativity in solving math problems of high self-efficacy male students are: a) at the stage of formulating problems, high self-efficacy male students are able to interpret the problem by illustrating what is known in the form of pictures according to their understanding through writing. b) at the stage of planning problem solving, high self-efficacy male students are able to plan appropriate ideas or methods that will be used to answer the given problem, c) at the stage of generating problems, self-efficacy male students students with high self-efficacy are able to do calculations through ideas or previously planned methods. 2) the profile of creativity in solving mathematical problems of female students with high self-efficacy are: a) at the stage of formulating problems, female students with high self-efficacy are able to collect and organize information to understand problems according to their understanding through writing, b) at the stage of planning problem solving, female students with high self-efficacy are able to plan ideas or appropriate methods that will be used to answer problems, c) at the stage of producing, female students with high self-efficacy are able to answer problems through ideas that are planned as before. 3) the profile of creativity in solving mathematical problems of male students with low self-efficacy are: a) at the stage of formulating problems, male students with low self-efficacy are able to collect and organize information to understand the problem, b) at the planning stage, students boys with low self-efficacy are able to plan ideas, c) at the stage of generating, male students with low self-efficacy are able to do the correct calculations through formulas or previously planned methods. 4) the profile of creativity in problem solving in female students with low self-efficacy: a) at the stage of formulating, women with low self-efficacy do not understand the problem as a whole because they only quote the information written in the questions, b) at the planning stage, women with low self-efficacy has not been able to plan the right ideas or methods that will be used to answer the given problems, c) at the generating stage, women with low self-efficacy are not able to do calculations correctly through ideas or methods. pre-planned way.